A Rapid Ethnography to Inform a Biobehavioural HIV Preventions Study Among Venezuelan Migrant Sex Workers in Peru: A Protocol of Formative Multidisciplinary Methods - Julien Brisson; Franceska León Morris; Kelika A. Konda; Alfonso Silva-Santisteban; Amaya Perez-Brumer (International Journal of Qualitative Methods, 2024)
The Venezuelan refugee crisis has triggered Latin America’s largest mass migration, displacing over a fifth of the country’s population. A significant number of migrants have sought refuge in neighboring countries like Peru. Within this context, Venezuelan migrants confront an array of vulnerabilities, including xenophobia and economic hardship, which have compelled some to sex work for their livelihoods. Venezuelan sex workers (VSWs) in Peru face amplified challenges, including heightened risks for HIV and sexually transmitted and blood-borne infections (STBBIs) and exposure to various forms of violence. Addressing the urgent need to comprehend and enhance HIV and STBBI preventive services tailored to this marginalized group in Peru’s capital is paramount. Our biobehavioural HIV prevention study combines sequential mixed methods: we start with a rapid ethnography, followed by semi-structured interviews and finally incorporate cross-sectional surveys with HIV and STBBI testing. The present study protocol presents the integrated and initial rapid ethnographic component of the study which explores the dynamics of street-based sex work in Lima and the sociocultural narratives surrounding VSWs. Data collection will involve systematic fieldnote taking including non-person photos during in-person and virtual participant observation. This comprehensive approach will provide a nuanced understanding of the complex landscape of sex work and HIV/STBBI vulnerabilities among VSWs in Lima. The rapid ethnography endeavors to offer valuable insights that can underpin evidence-based healthcare interventions, specifically tailored to cater to the unique requirements of this marginalized population.